Comparison of HbA1c Measurements using 3 Methods in 75 Patients Referred to One Outpatient Department - Roth, Johannes; Müller, Nicolle; Lehmann, Thomas; Böer, Klas; Löbel, Sven; Pum, Joachim; Müller, Ulrich Alfons (Experimental and Clinical Endocrinology & Diabetes, 2018)
Objective HbA1c is the most important surrogate parameter to assess the quality of diabetes care and is also used for the diagnosis of diabetes mellitus (DM) since 2010. We investigated the comparability of 3 HbA1c methods in the city of Jena (Germany).Methods The HbA1c determination was carried out in 50 healthy subjects and 24 people with DM (age 51.2±16.3 years, HbA1c 6.8±2.2%) with 3 different hemoglobin A1c testing methods at 4 locations in one city. Our laboratory (HPLC method) served as a reference for comparing the results. All methods are IFCC standardized and all devices are certified by the interlaboratory test.Results The mean HbA1c of people without diabetes was: laboratory A (TOSOH G8, HPLC) 5.7±0.3%; laboratory B (TOSOH G8, HPLC) 5.5±0.3%, laboratory C (VARIANT II) 5.2±0.3%; laboratory D (COBAS INT.) 5.6±0.3%. All differences are significant (p=0.001).The mean HbA1c of patients with mild to moderate elevated HbA1c was: Laboratory A 7.5±0.9%; B 7.3±1.0%; C 7.0±0.9%; D 7.5±1.1%. Differences are significant (p=0.001) except between laboratory A and D (p=0.8).The mean HbA1c of patients with massively increased HbA1c was: laboratory A 11.5±1.8%; laboratory B 11.4±1.8%; laboratory C 10.8±1.6%; laboratory D 11.5±1.5%. Differences between laboratory A and C, as well as between C and D were significant (p=0.001).Conclusion The mean IFCC standardized HbA1c from 75 people differs by up to 0.5% absolute between 4 laboratories. This difference is clinically significant and may lead to misdiagnosis and wrong treatment decisions, while HbA1c value from one patient were analyzed in different laboratories within a short time.
Keywords: diabetes mellitus; HbA1c; measurement methods; comparability